Woman Exploitation Reflected in Memoirs of A Geisha by Arthur Golden - Rida Fahas (Universitas PGRI Madiun, 2020)
Memoirs of a Geisha is one of literary work that describes the issues about the development of Japan civilization and the growth of a certain profession called Geisha. This research aims to analyze the woman exploitation reflected in Memoirs of A Geisha. Method that is used to analyze the woman exploitation is qualitative method. As the object of the research, Memoirs of a Geisha is also become the primary data source. This novel is written by Arthur Golden and printed in 1997 by Vintage Books, a division of Random House, Inc., New York. The secondary data sources are the author’s biography and books of literary theory. In analyzing the data, the researcher used library research and descriptive analysis. In analyzing the woman exploitation, the writer uses feminist perspective. The term that will be analyzed consists of woman’s position, woman’s role, woman’s participation, and woman’s right. The result of the research shows that women are exploited in male-controlled. It also shows that woman must fight to get their right. Woman must be clever and brilliant to have the freedom. Memoirs of a Geisha is very interesting novel to analyze. Therefore, it is possible to be a good novel to read and take the moral lesson from it.